The nexus between top management support on change management, cloud ERP implementation, and performance of SMEs - Jayeola, Olakunle; Sidek, Shafie; Sanyal, Shouvik; Hasan, Md. Meraj; Singh, Amarendra Pratap; Hasan, Syed Inamul (Richtmann publishing, 2022)
Top management support (TMS) is a critical success factor in cloud computing (CC) implementation and firm performance. However, extant empirical research on these relationships has obtained mixed findings due to earlier studies focusing on a one-dimensional TMS construct with diverse measurement items that muddle up different behaviours of top management. TMS is typically a multi-dimensional construct, such as TMS change management (TMSCM), TMS resource provision (TMSR), and TMS vision sharing (TMSV). The aim of this study is to examine a specific TMS dimension, TMSCM, on cloud ERP implementation and, further, to measure the effect of TMSCM on the financial performance of manufacturing small and medium-sized enterprises (SMEs) through the mediating effect of cloud ERP implementation. The proposed research model was validated using partial least squares structural equation modelling (PLS-SEM) with a sample of 204 Malaysian manufacturing SMEs. Results reveal that TMSCM significantly impacts cloud ERP implementation and financial performance. Moreover, cloud ERP implementation is a significant driver of financial performance, and it partially mediates the relationship between TMSCM and financial performance. Contributing to disentangling the mixed findings of TMS impact on cloud ERP implementation and firm performance, this study also generates insights for practitioners that they need to balance TMSCM and cloud ERP implementation to improve the financial performance of SMEs.